2012
DOI: 10.1016/j.talanta.2012.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Development of a fast capillary electrophoresis method for determination of carbohydrates in honey samples

Abstract: In this study, the determination of fructose, glucose and sucrose by capillary electrophoresis (CE) was investigated. The tendency of the analyte to undergo electromigration dispersion and the buffer capacity were evaluated using the Peakmaster(®) software and considered in the optimization of the background electrolyte, which was composed of 20 mmol L(-1) sorbic acid, 0.2 mmol L(-1) CTAB and 40 mmol L(-1) NaOH at pH 12.2. Under optimal CE conditions, the separation of the substances investigated was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 24 publications
0
23
0
2
Order By: Relevance
“…As a result, levels of the three saccharides were quantified in all samples. Same saccharides were determined in seven honey samples . The quantitative results revealed that fructose was the major sugar in honey samples (33.65–45.46 g /100 g) followed by glucose (22.34–35.39 g/100 g).…”
Section: Carbohydratesmentioning
confidence: 99%
“…As a result, levels of the three saccharides were quantified in all samples. Same saccharides were determined in seven honey samples . The quantitative results revealed that fructose was the major sugar in honey samples (33.65–45.46 g /100 g) followed by glucose (22.34–35.39 g/100 g).…”
Section: Carbohydratesmentioning
confidence: 99%
“…An option to solve the lack of chromophores is the use of indirect UV detection. For instance, Rizelio et al developed a CE methodology for the determination of fructose, glucose, and sucrose in seven multifloral honey samples. A satisfactory and rapid separation (less than 2 min) was achieved using a BGE comprised of 20 mM sorbic acid, 0.2 mM CTAB, and 40 mM sodium hydroxide (pH 12.2).…”
Section: Carbohydratesmentioning
confidence: 99%
“…Cetyltrimethylammonium bromide (CTAB), a single-chain surfactant, has been extensively studied as dynamic modifier to obtain a reversal of the EOF in CE [38][39][40] and ME [41][42][43]. Thus, borosilicate glass microchips were modified with CTAB for the determination of inorganic ions [41] , or arsenic species [42] as well as a PMMA microchip for the determination of urine markers [43].…”
Section: Introductionmentioning
confidence: 99%
“…Reversed EOF has been used in capillary and microchip electrophoresis for the separation of small inorganic and organic anions [33], acidic plant hormones [34], basic proteins [35], and peptides [36]. Apart from changing the polarity of the high-voltage electrodes, a positive charge should be generated on the wall and dynamic coating with cationic surfactants has been employed with this aim [37].Cetyltrimethylammonium bromide (CTAB), a single-chain surfactant, has been extensively studied as dynamic modifier to obtain a reversal of the EOF in CE [38][39][40] and ME [41][42][43]. Thus, borosilicate glass microchips were modified with CTAB for the determination of inorganic ions [41] , or arsenic species [42] as well as a PMMA microchip for the determination of urine markers [43].…”
mentioning
confidence: 99%